1998
DOI: 10.1094/pdis.1998.82.12.1312
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Management of Sclerotinia Blight in Peanut: Utilizing Canopy Morphology, Mechanical Pruning, and Fungicide Timing

Abstract: Sclerotinia blight of peanut, caused by Sclerotinia minor, generally becomes severe only after vines meet in the row middles and a dense canopy develops. Dense foliage appears to support a microclimate conducive to the colonization of peanut limbs by S. minor. Removal of excess foliage before and during a Sclerotinia blight epidemic on the susceptible genotype NC 7 has been shown to reduce the rate of disease progress. Field tests in 1993 and 1994 examined control of Sclerotinia blight among four peanut genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…However, the pods of bunch/erect plants develop at the same time, promoting early maturation. The growth habit of peanut affects the implementation of agrotechnology such as mechanical cultivation and disease management (Butzler et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…However, the pods of bunch/erect plants develop at the same time, promoting early maturation. The growth habit of peanut affects the implementation of agrotechnology such as mechanical cultivation and disease management (Butzler et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Butzler et al (1998) stated that plant-toplant infection of Sclerotinia blight of peanut (Sclerotinia minor Jagger) occurs after canopy closure and concluded that further spread of the disease could successfully be reduced by mowing excess foliage after disease pressure was evident. By the introduction of mycorrhizal fungi the incidences of disease was also lower in mycorrhizal treated groundnut plant than there non-mycorrhizal pathogenic plants.…”
Section: Total Biomassmentioning
confidence: 99%
“…The application of benomyl in conjuntion with the pruning of peanut vines increased stem rot control (Backman et al, 1975). Likewise, the application of iprodione following pruning has improved control of Sclerotinia blight (Bailey and Brune, 1997;Butzler et al, 1998). Implements designed to open the canopy have been used to concentrate fungicides near the crown area.…”
Section: Improving Fungicide Deposition and Efficacy Via Application mentioning
confidence: 99%